Sundarban mangroves: diversity, ecosystem services and climate change impacts - Neogi, Sucharit Basu; Dey, Mouri; Kabir, S M Lutful; Masum, Syed Jahangir H; Kopprio, German; Yamasaki, Shinji; Lara, Rubén (Asian Journal of Medical and Biological Research, 2017)
The Bengal delta coast harboring the famous Sundarban mangroves is extremely vulnerable to climate change. Already, salinity intrusion, increasing cyclones and anomalies in rainfall, and temperature, are causing many social and livelihood problems. However, our knowledge on the diversified climate change impacts on Sundarban ecosystems services, providing immense benefits, including foods, shelters, livelihood, and health amenities, is very limited. Therefore, this article has systematically reviewed the major functional aspects, and highlights on biodiversity, ecosystem dynamics, and services of the Sunderban mangroves, with respect to variations in climatic factors. The mangrove ecosystems are highly productive in terms of forest biomass, and nutrient contribution, especially through detritus-based food webs, to support rich biodiversity in the wetlands and adjacent estuaries. Sundarban mangroves also play vital role in atmospheric CO2 sequestration, sediment trapping and nutrient recycling. Sea level rise will engulf a huge portion of the mangroves, while the associated salinity increase is posing immense threats to biodiversity and economic losses. Climate-mediated changes in riverine discharge, tides, temperature, rainfall and evaporation will determine the wetland nutrient variations, influencing the physiological and ecological processes, thus biodiversity and productivity of Sundarban mangroves. Hydrological changes in wetland ecosystems through increased salinity and cyclones will lower the food security, and also induce human vulnerabilities to waterborne diseases. Scientific investigations producing high resolution data to identify Sundarban?s multidimensional vulnerabilities to various climatic regimes are essential. Sustainable plans and actions are required integrating conservation and climate change adaptation strategies, including promotion of alternative livelihoods. Thus, interdisciplinary approaches are required to address the future climatic disasters, and better protection of invaluable ecosystem services of the Sunderban mangroves. Asian J. Med. Biol. Res. December 2016, 2(4): 488-507